Declining trends of students’ enrollment in the faculty of education at Jayaprithvi Multiple Campus - Oli, Sher Bahadur (Journal of Jayaprithvi Multiple Campus, 2025)
This study investigates the declining trend of students’ enrollment in the Faculty of Education at Jayaprithvi Multiple Campus over a five-year period, spanning from 2075 to 2079 B.S. (2018–2022). Drawing on institutional data, the research highlights a significant reduction in the number of students enrolled in the B.Ed first semester, with figures dropping from 140 in 2075/2076 to just 80 in 2079/2080—an overall decrease of 42.86%. A detailed semester-wise and subject-specific breakdown reveals that Health Education remains the most popular specialization, consistently enrolling the majority of students, while other subjects such as English, Nepali, and Population Education experience notably lower and declining enrollment. The study identifies key socio-cultural and institutional factors behind this downward trend. Notably, approximately 75% of the enrolled students are female, and a considerable number discontinue their studies due to early marriage, which imposes domestic responsibilities and limits their educational continuity. Additionally, confusion and lack of awareness surrounding the semester system—particularly its continuous assessment model, credit structure, and academic rigor—have contributed to student dissatisfaction and dropout. These findings underscore the urgent need for strategic interventions aimed at improving student retention and engagement. Recommendations include raising community awareness about the importance of girls’ education, providing orientation programs on the semester system, and implementing student support mechanisms. Addressing these challenges is crucial for reversing the enrollment decline and ensuring equitable access to higher education in the region.